2004 IEEE International Conference on Systems, Man and Cybernetics (IEEE Cat. No.04CH37583)
DOI: 10.1109/icsmc.2004.1400762
|View full text |Cite
|
Sign up to set email alerts
|

"Where am i?" acquiring situation awareness using a remote robot platform

Abstract: - K e y w o r d s :Situation awareness, human-robot interaction, HRI, urban search and rescue, humancomputer interaction, HCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 14 publications
1
79
0
Order By: Relevance
“…Scholtz et al (2004) used Endsley's (1988) Situation Awareness Global Assessment Technique (SAGAT) to determine robotic vehicle supervisors' awareness of when vehicles were in trouble and thus required closer monitoring or intervention. Yanco and Drury (2004) employed usability testing to determine (among other things) how well a search and rescue interface supported use by first responders.…”
Section: Introductionmentioning
confidence: 99%
“…Scholtz et al (2004) used Endsley's (1988) Situation Awareness Global Assessment Technique (SAGAT) to determine robotic vehicle supervisors' awareness of when vehicles were in trouble and thus required closer monitoring or intervention. Yanco and Drury (2004) employed usability testing to determine (among other things) how well a search and rescue interface supported use by first responders.…”
Section: Introductionmentioning
confidence: 99%
“…In usability experiments [2], we observed the robot bump obstacles in the environment an average of 2.6 times per run. Of the 29 hits during all of the four subjects' runs, 12 or 41% of the hits were on the rear of the robot.…”
Section: Adding Sensors To the Rear Of The Robotmentioning
confidence: 99%
“…The operator also needs to use the video to locate victims in the environment. In a study of how operators acquire situation awareness, we found that an average of 30% of run time was spent looking around the environment to the exclusion of all other tasks (i.e., just looking, not navigating at the same time) [2].…”
Section: Designing a New Interfacementioning
confidence: 99%
See 2 more Smart Citations